Research handbook on the ombudsman - Hertogh, Marc, 1968-; Kirkham, Richard (Research handbooks in law and politics, 2018)
The public sector ombudsman has become one of the most important administrative justice institutions in many countries around the world. This international and interdisciplinary Research Handbook brings together leading scholars and practitioners to discuss the state-of-the-art research on this increasingly prominent institution. Traditionally, research on the ombudsman has been conducted from a purely prescriptive or (legal) descriptive perspective, mainly focusing on the ombudsman 'in the books'. By contrast, this book illustrates how empirical research may contribute to a better understanding of the ombudsman 'in action'. It uses new empirical studies and competing theoretical explanations to critically examine important aspects of the ombudsman's work. The Research Handbook is organized in to four parts: fundamentals of the ombudsman; the evolution of the ombudsman; evaluation of the ombudsman; and the ombudsman office and profession. Featuring case studies from Europe, Canada, Asia, Africa, Latin America and Australia, chapters provide a comprehensive global perspective on the issues at hand. This unique Research Handbook will be of great value to researchers in the fields of public law, socio-legal studies and alternative dispute resolution who have an interest in the ombudsman. It will also be a valuable resource for policymakers and practitioners, particularly those working within ombudsman offices.